DETECÇÃO OPORTUNA DE SINAIS DE SOFRIMENTOS PSÍQUICOS EM BEBÊS NA ATENÇÃO PRIMARIA: UMA EXPERIÊNCIA FORMATIVA - Bastos, Maiara Cristiani Perini (2024)
This dissertation deals with the preparation of nursing professionals, especially those who work with childcare in Family Health Strategies, in relation to the psychic aspects of babies' development, based on the Reference Indicators for Child Development script. The study is part of the Sustainable Development Goals, especially Goal 3: “Ensure a healthy life and promote well-being for all, at all ages”, as well as the Research Priorities Agenda of the Ministry of Health, Axis 14, “Maternal and child health”. Objectives: Implement and evaluate a professional training course in the form of training meetings, on the Reference Indicators for Child Development, with a view to expanding the knowledge of nursing professionals regarding childcare consultations in the Public Health Service; Identify the nursing team’s prior knowledge about the psychological aspects during the baby’s development; Understand the perception of nursing professionals in relation to nurses' actions regarding the psychological aspects of development in childhood; Disseminate and expand up-to-date scientific knowledge with a view to identifying signs of psychological distress in babies. Methodological Course: Qualitative systematized study, in which seven nurses who attend childcare consultations in a Basic Health Unit and two babies participated, in the city of Três de Maio-RS. The first stage was a group interview with the professionals invited to participate in the course. Based on the data obtained, the researcher outlined the construction of the theoretical and pedagogical proposal for implementing the course. It took place from May to June/2023, through five training meetings, every two weeks, based on the four theoretical axes proposed by the Reference Indicators for Child Development script. In the end, an instrument was applied to evaluate the training proposal offered and the perception of professionals. Afterwards, with a view to associating theory presented in the course with practice, the researcher followed, together with nursing, two clinical cases treated in childcare. Results: this study highlighted the lack of knowledge among nursing professionals about the psychological aspects of child development. The proposal for the training meetings was successful, according to the participants' assessment, in terms of the use of content and methodology. The short-term training course is a technical product, according to Qualis Technical Production of the Coordination for the Improvement of Level Personnel (CAPES), item 8, T=75 points. This classification covers creating, organizing and teaching a course at different training levels. Final Considerations: this study confirms the importance of disseminating knowledge about the signs of baby's psychological distress, especially to health professionals who work in childcare, with a view to timely detection and immediate intervention in the Basic Care Unit itself. Health or with referral to a specialized professional. Product Applicability: the proposed course model can be replicated in Basic Health Units in other municipalities and with other practical specialties working with babies and their relatives. The impact is expected to be offered by courses in various health units considered as a prevention strategy in early childhood. Therefore, investing in the training of the nursing team, replicating the course, could also have an impact on reducing public resources allocated to the treatment of psychological disorders in childhood.